# Solve the formula: E/R+r=1, solve for RPlease explain how to solve this. This problem has me very confused.

### 1 Answer | Add Yours

We do this just like R was a number

`E/R+r=1`

`E/R+r - r = 1 - r` subtract r from both sides

`E/R = 1 - r` simplify

` E/R * R/1 = (1-r)R/1` Multiply both sides by R

`E = (1 - r)R` simplify

`E/(1-r) = (R(1 - r))/(1 - r)` Divide both sides by 1-r

`E/(1-r) = R` simplify

`R = E/(1-r)` referse direction of equality `a=b => b=a`

Solution `R = E/(1 - r)`

Unless you meant `E/(R-r) = 1`

`E/(R-r) * (R-r)/1 = 1(R - r)/1` Multiply both sides by R-r

` E = (R - r)` Simpilfy

`(R - r) = E` Reverse

`R - r + r = E + r` Add r to both sides

`R = E + r` Simplify To get answer

If equation is `E/R - r = 1` Solution is `R = E/(1 - r) = -E/(r - 1)`

If equation is `E/(R - r) = 1` Solution is `R = E + r`